2016
DOI: 10.3892/or.2016.4958
|View full text |Cite
|
Sign up to set email alerts
|

Coix seed emulsion synergistically enhances the antitumor activity of gemcitabine in pancreatic cancer through abrogation of NF-κB signaling

Abstract: Clinical outcomes in patients with pancreatic cancer (PC) continue to be dismal, in part due to de novo and acquired chemoresistance. In the present study, we provide preclinical evidence that pre-treatment with coix seed emulsion, an injectable agent extracted from coix seeds, synergistically sensitized PC cell lines (BxPC-3, PANC-1 and AsPC-1) to gemcitabine, both in vitro and in vivo. Such pretreatment led to significant induction of pro-apoptosis proteins, including caspase-3, cleaved-PARP and Bax (P<0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…In vitro cell viability results indicated that coix seed extract can enhance the cytotoxicity of gemcitabine against BxPC3 luc and PANC-1 cells and showed a clear degree of synergism (Figure 1, Supplementary Figure S7). Moreover, the animal study also demonstrated the synergistic effect of coix seed extract and gemcitabine against pancreatic tumor growth (Figure 3B) which is consisted with our in vitro data and other previous studies [28,30,32]. Zhang et al [32] found that the coix seed extract could prevent cisplatin resistance by inhibiting the ABCB1 and ABCC1 expression and enhance the sensitivity of cells to cisplatin in gastric cancer cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In vitro cell viability results indicated that coix seed extract can enhance the cytotoxicity of gemcitabine against BxPC3 luc and PANC-1 cells and showed a clear degree of synergism (Figure 1, Supplementary Figure S7). Moreover, the animal study also demonstrated the synergistic effect of coix seed extract and gemcitabine against pancreatic tumor growth (Figure 3B) which is consisted with our in vitro data and other previous studies [28,30,32]. Zhang et al [32] found that the coix seed extract could prevent cisplatin resistance by inhibiting the ABCB1 and ABCC1 expression and enhance the sensitivity of cells to cisplatin in gastric cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…Coix seed extract was reported to enhance the anti-pancreatic cancer efficacy of gemcitabine in different preclinical studies [17,25,26,27] and phase II clinical trial in US [10]. Current molecular pharmacology studies have revealed that coix seed extract may show anti-pancreatic cancer activity through multiply mechanisms including inducing apoptosis and cell cycle arrest at G2/M phase [25,28], inhibition of NF-kB pathway [29,30] and PI3K/AKT pathway [31]. However, it remains unclear whether the coix seed extract could suppress ABC transporter mediated drug efflux which was induced by gemcitabine and enhance the efficacy of chemotherapy in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, modern medicine research has established that coix seed emulsion from Coisis semen combined with gemcitabine had a much greater antitumor effect than the effect of either agent alone in pancreatic cancer through abrogation of nuclear factor-kappa B signaling. [ 35 ] Another 2 components (Zedoary and Oldenlandia diffusa) also exhibit potential anticancer effects and restore the sensitivity of MCF-7/ADR (doxorubicin-resistant MCF-7 breast cancer cells) and A549/Taxol cells, modulating the multidrug resistance phenotype and the function of P-glycoprotein in human breast cancer cells. [ 36 , 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…For examples, NF-κB activation is shown in Figures 1 and 5A in publication by Toriuchi et al [2], Figure 7A in publication by Zhang et al [3], and Figure 4C in publication by Qian et al [4]. It is known that cell lines with same name used by different labs over years may have altered phenotypes.…”
Section: In Response: We Thank Prof Shusen Zheng and Colleagues For mentioning
confidence: 99%